IoT Based Soil Nutrient Development Monitoring System for Smart Pineapple Farming using Firebase - Kannapan, Adaikan; Mohamad, Elmy Johana (Evolution in Electrical and Electronic Engineering, 2023)
This system is optimized to monitor seven soil properties in real-time with an implementation of single soil sensor powered by renewable energy. A dashboard system is designed for accessing information regarding crops anywhere. End users will be able to observe the current condition of crops from any desired location and time. Implementation of a seven in one soil sensor to a Wi-Fi compatible microcontroller module which is configured to a database can be accessed through a designed application. Data collection in this research is carried out manually with a time interval of five seconds. A master unit is feeds real time updates database while the client is placed in the desired observing area. Both units communicate through a long-range wide area network technology. The designed dashboard system retrieves real time data from the connected database. Real-time data feeds will be interrupted if Wi-Fi connection is disrupted under any circumstance. Farmers or any end users will be highly benefitted by this system for agricultural purpose as real-time crop conditions observation ensures that the growth of crops are not affected if maintained accordingly. The dashboard system can be improvised by integrating a data analyzation technique for detailed crop reviews.